Apakah Ukuran Perusahaan Sebagai Variabel Moderasi? - Eny Maryanti; Sarwenda Biduri; Herlinda Maya K. (Akuntansi : Jurnal Akuntansi Integratif, 2022)
This study aims to examine whether firm size can moderate the relationship, profitability and level of sales to profit growth in consumption sector manufacturing companies listed on the Indonesian stock exchange for the 2018-2020 period. The sampling technique using purposive sampling obtained 11 companies that meet the research criteria. This research is a panel analysis of regression data using a eviews 12. The results showed that the model that was suitable for this study was to use commond effects compared to other models. The size of the company cannot be used as a moderating variable on the relationship between profitability, liquidity and sales growth on profit growth.